The Phenomenon of an Empty Frame in the Art of the Modern Times - Khachaturov, Sergey V. (Actual Problems of Theory and History of Art, 2014)
The article is devoted to the phenomenon of “inclusion in the frame” in the art of the modern times. Making a retrospective journey into the depths of centuries, the author tries to prove that frame is included into the design of an artwork not as a decoration or an addition, but as the essential part of it. The paper focuses on the theme of an empty frame which releases to the greatest degree creative energy and activity of the audience as a full-fl edged participant of an art event.
Keywords: Frame; framing; emptiness in art; modern and contemporary art; art theory